2020
DOI: 10.1111/ajt.15747
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islets engineered with a FasL protein induce systemic tolerance at the induction phase that evolves into long-term graft-localized immune privilege

Abstract: We have previously shown that pancreatic islets engineered to transiently display a modified form of FasL protein (SA‐FasL) on their surface survive indefinitely in allogeneic recipients without a need for chronic immunosuppression. Mechanisms that confer long‐term protection to allograft are yet to be elucidated. We herein demonstrated that immune protection evolves in two distinct phases; induction and maintenance. SA‐FasL‐engineered allogeneic islets survived indefinitely and conferred protection to a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 63 publications
(111 reference statements)
6
22
0
Order By: Relevance
“…Importantly, the engineering of islets with SA‐CD47 did not negatively impact their viability, metabolic activity, or insulin secretion. These findings are consistent with our published studies transiently displaying the SA‐FasL protein on the surface of islets for the regulation of alloreactive immune responses 35,55 . In an in vitro xenogeneic system, SA‐CD47‐engineered rat cells overcame phagocytosis by mouse macrophages.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, the engineering of islets with SA‐CD47 did not negatively impact their viability, metabolic activity, or insulin secretion. These findings are consistent with our published studies transiently displaying the SA‐FasL protein on the surface of islets for the regulation of alloreactive immune responses 35,55 . In an in vitro xenogeneic system, SA‐CD47‐engineered rat cells overcame phagocytosis by mouse macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with our published studies transiently displaying the SA-FasL protein on the surface of islets for the regulation of alloreactive immune responses. 35,55 In an in vitro xenogeneic system, SA-CD47-engineered rat cells overcame phagocytosis by mouse macrophages. This observation is consistent with studies F I G U R E 4 SA-CD47 engineering protects islets from destruction by IBMIR in an in vitro loop assay.…”
Section: Sa-cd47 Display Alters the Intrahepatic Infiltration Of Inflammatory Cells And Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inherent affinity for the liver, this system has been previously used in a study of lipid metabolism, the liver being the major source of plasma apolipoproteins [ 27 , 28 ]. Although under some pathological conditions the liver may be susceptible to apoptosis triggered by the Fas/FasL interaction [ 26 ], numerous studies have shown that therapeutic use of FasL in vivo does not cause liver toxicity [ 29 , 30 ]. Human CAR homologs are prevalently expressed in various species, including mice, rats, and pigs [ 31 , 32 ]; therefore, we chose a line of endothelial cells that are inherently resistant to FasL-induced apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, islets derived from animals (porcine islets) can solve the problem of organ shortage, but problems associated with strong rejection need to be solved in the future [ 43 ]. The mechanism of rejection following xenogeneic transplantation is extraordinarily complicated, as shown by the small number of reports of successful induction of xenografts [ 44 , 45 ]. In the present study, euglycemia was maintained in the TEC by an effective dual antibody treatment (anti-CD45RB plus anti-MR-1) after xenotransplantation from rats to C57 mice.…”
Section: Discussionmentioning
confidence: 99%